Application of quality control circle activities to improve the implementation of“one-doctor-one-patient”in the outpatient department of an ophthalmology hospital (运用品管圈提高眼病专科医院门诊“一医一患”制度执行率) - LAN Yanfei (兰艳飞); FAN Tianli (樊田莉); XING Xiaoying (邢晓英); ZHANG Yu (张瑜); ZHAO Yan (赵燕); LI Wenjing (李文婧) (中西医结合护理)
Objective To evaluate the of quality control circle (QCC) activities in improving the implementation of “one-doctor-one-patient” in the outpatient department of ophthalmology hospital. Methods A QCC team was established to conduct QCC activities. The current situation and factors of errors in the implementation of “one-doctor-one-patient” in the outpatient department were analyzed. Targeted nursing countermeasures by using QCC management tools were carried out to establish a standard procedure of outpatient management. Results The implementation rate of “one-doctor-one-patient” in the outpatient department was increased formation 41. 67% to 91. 56% . Conclusion The QCC is an effective tool to improve the outpatient consultation process and quality of nursing service in the outpatient department of an ophthalmology hospital. (目的 探讨品管圈活动提高眼科医院门诊“一医一患”制度的执行率的效果。方法 成立品管圈小组, 通过主题选定、拟定活动计划、目标设定、现状把握与目标设定、解析与真因验证、对策拟定、对策实施、效果确认、标准化就诊流程的建立、检讨与改进的步骤来完成活动, 从而建立一个标准化作业流程。结果 门诊“一医一患”执行率由41. 67%上升至91. 56%。结论 运用品管圈改进门诊就诊流程, 可以提高医疗质量与就诊效率, 改善护理服务品质。)